Perspectives of student performance in the Health Sciences: how do physiology and professional modules compare? - Higgins-Opitz, Susan B; Tufts, Mark; Naidoo, Indirani; Essack, Sabiha Y (South African Journal of Higher Education, 2016)
Physiology has an anecdotal track record of having lower pass rates than other professional modules in the Health Sciences. The aim of this study was to compare the performance and associated contributory factors of students in physiology modules with professional modules at the same level of study by way of overall pass rates and average, maximum, and minimum marks for the period 2008 – 2010 stratified by programme/qualification, matriculation/National Senior Certificate achievement and language, the latter two serving as proxies for alternative access and previously disadvantaged students, respectively. There was a notable difference in the mean 2008 - 2010 pass rates of students from the different professional qualifications and students generally performed considerably better in their professional modules as compared with their performance in the physiology modules. The performance in Physiology modules of English first language students was not significantly different from that of English second language students. The implications of these findings require further discourse on inter alia issues around physiology teaching, student learning modes, admission criteria, student preparedness for University and student monitoring and support mechanisms. There also needs to be a greater interaction between physiologists and health professionals involved in the curriculum design.